2019
DOI: 10.1155/2019/1201927
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Optimization of the Seeding Process of Adipose Stem Cells on the Polycaprolactone Scaffolds

Abstract: The purpose of the current study was to evaluate the usefulness of adipose-derived stem cells (ASCs) for bone injury therapy. Lipoaspirates were collected from the abdomen regions of 17 healthy female donors (mean age 49 ± 6 years) using Coleman technique or Body-jet liposuction. In the present study, the primary objective was the in vitro characteristics of human ASCs. The secondary objective was the optimization of the cell seeding process on 3D-printed scaffolds using polycaprolactone (PCL) or polycaprolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…When rabbit ADSCs (rADSCs) or their secretome were injected into the knees of rabbits with cartilage lesions, better cartilage regeneration was achieved in the ADSC group than in the secretome group 82 , indicating that ADSCs may be more effective in the repair of cartilage damage than their secretome. In addition, many types of biomaterial scaffolds based on chitosan, fibrin, atelocollagen, and decellularized cartilage have been used as carriers to provide a 3D culture environment for ADSCs, which could support the survival, proliferation and differentiation of ADSCs 83 , 84 . For example, Boyer et al 85 seeded hADSCs on an injectable hydrogel composed of silanized hydroxypropyl cellulose to repair osteochondral defects in dogs and demonstrated satisfactory effects after 4 months.…”
Section: Tissue Source-dependent Variation In Mscs For Cartilage Repamentioning
confidence: 99%
“…When rabbit ADSCs (rADSCs) or their secretome were injected into the knees of rabbits with cartilage lesions, better cartilage regeneration was achieved in the ADSC group than in the secretome group 82 , indicating that ADSCs may be more effective in the repair of cartilage damage than their secretome. In addition, many types of biomaterial scaffolds based on chitosan, fibrin, atelocollagen, and decellularized cartilage have been used as carriers to provide a 3D culture environment for ADSCs, which could support the survival, proliferation and differentiation of ADSCs 83 , 84 . For example, Boyer et al 85 seeded hADSCs on an injectable hydrogel composed of silanized hydroxypropyl cellulose to repair osteochondral defects in dogs and demonstrated satisfactory effects after 4 months.…”
Section: Tissue Source-dependent Variation In Mscs For Cartilage Repamentioning
confidence: 99%
“…The overall low cell attachment could be explained by the imperfection of the chosen seeding method, considering the fact that the scaffolds were not well fixed at the bottom of the wells and consequently a certain amount of the cells could slip under scaffolds after seeding. In our future experiments we will try to prevent this by anchoring the disc shaped matrices with metal rings or certain non-toxic adhesives [ 31 ]. This shortcoming of the cell seeding technique was actually the main reason why we performed all the absorbance assays in sextuplicate.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies had shown that without adipose-inductive scaffolds and microenvironment, transplantation of ASCs does not generate adipose tissue ( Acil et al, 2014 ; Kurzyk et al, 2019 ). However, we found that they played an important role in activating the adipoinduction potential of the ECM and microenvironment.…”
Section: Discussionmentioning
confidence: 99%